Pelatihan Manajemen Pendidikan Multikultural (Multicultural Education Management): Strategi dalam Penanaman Nilai-Nilai Agama dan Budaya Santri Masa Kini : Studi Kasus di Pondok Modern Darul Hikmah Tulungagung - Aminatul Zahroh; Halimatus Sa’dyah; Purwanto Purwanto; Muhammad Anasrulloh; Pendik Hanafi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the diversity of students found in Islamic boarding schools. Islamic boarding schools are an appropriate base for instilling religious and cultural values ​​in students. Therefore, differences in race, ethnicity, customs, social class, and culture are not addressed with exclusive and fanatical attitudes to prevent conflict. The purpose of this research is to provide multicultural education management training in Islamic boarding schools as an educational alternative that can be applied to address the problems faced by students and the current multicultural society, so that each student can live side by side despite differences in harmony and peace in accordance with religious and cultural values. The research method used is qualitative with the PAR (Participatory Action Research) model. For data collection, in-depth interviews, participant observation, and documentation were used. The results of this study are that multicultural education management training is a preventive effort to address various problems and becomes a real solution to existing problems in Islamic boarding schools related to the religious and cultural values ​​of students. In addition to being an alternative means of solving problems, multicultural education management training is also a means of fostering students so that they do not lose their cultural roots in accordance with religious values. Thus, the implementation of multicultural education management training can be said to be successful if it can produce students who have a tolerant attitude, are not hostile, and do not conflict caused by differences in culture, ethnicity, customs, social class, abilities, and others.